Female bonobos use copulation calls as social signals - Clay, Zanna; Pika, Simone; Gruber, Thibaud; Zuberbühler, Klaus (My University, 2011)
During mating events, females of many primate species produce loud and distinct vocalizations known as ‘copulation calls’. The adaptive significance of these signals is considered to be in promoting the caller’s direct reproductive success. Here, we investigated copulation calling in bonobos (Pan paniscus), a species in which females produce these vocalizations during sexual interactions with partners of both sexes. Females were more likely to call when mating with males than with females. We also observed a positive relationship between the likelihood of calling and partner rank, regardless of partner sex. Sexual activity generally increased with swelling size (an indicator of reproductive state) and, during their peak swelling, females called more with male than with female partners. Female bonobos are unusual among the nonhuman primates in terms of their heightened socio-sexuality. Our results suggest that in this species, copulation calls have undergone an evolutionary transition from a purely reproductive to a more general social function, reflecting the intrinsic evolutionary links between vocal behaviour and social cognition.
Keywords: primate vocalization; sexual selection; social intelligence